1792 N.Y. Laws 227 - (:unkn) unknown (My University, 1786)
Defined the New York militia as "every able- bodied male person, being a citizen of this state, or of any of the United States, and residing in this state (except such persons as are herein after excepted) and who are of the age of sixteen, and under the age of forty-five years." The arms were "a good musket or firelock," 24 bullets, "a sufficient bayonet" and other standard items."
Keywords: MILITIAS; DEFINITIONS